2017
DOI: 10.1038/nn.4616
|View full text |Cite
|
Sign up to set email alerts
|

Antipsychotic-induced Hdac2 transcription via NF-κB leads to synaptic and cognitive side effects

Abstract: Antipsychotic drugs remain the standard for schizophrenia treatment. Despite their effectiveness in treating hallucinations and delusions, prolonged exposure to antipsychotic medications leads to cognitive deficits in both schizophrenia patients and animal models. The molecular mechanisms underlying these negative effects on cognition remain to be elucidated. Here we demonstrate that chronic antipsychotic drug exposure increases nuclear translocation of NF-κB in both mouse and human frontal cortex, a trafficki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
118
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 90 publications
(129 citation statements)
references
References 79 publications
10
118
0
1
Order By: Relevance
“…These data suggest that antipsychotic medication usage did not drive [ 11 C]Martinostat uptake alterations in these regions. As antipsychotic drug exposure was shown to increase HDAC2 protein expression in the frontal cortex (29,53,54) of rodents, [ 11 C]Martinostat uptake differences may be more pronounced when comparing controls with medication-free subjects with SCZ/SAD.…”
Section: Resultsmentioning
confidence: 99%
“…These data suggest that antipsychotic medication usage did not drive [ 11 C]Martinostat uptake alterations in these regions. As antipsychotic drug exposure was shown to increase HDAC2 protein expression in the frontal cortex (29,53,54) of rodents, [ 11 C]Martinostat uptake differences may be more pronounced when comparing controls with medication-free subjects with SCZ/SAD.…”
Section: Resultsmentioning
confidence: 99%
“…novel-object recognition (noR) test. NOR test was assessed as previously reported 65,66 . Briefly, mice were given a 10-min acquisition trial and a 5-min recognition trial, separated by a 24 h inter-trial return to their home cage.…”
Section: Radioligand Binding [ 3 H]mentioning
confidence: 99%
“…The injected doses were as follows: DOI, 1 mg/kg; clozapine, 1.5 mg/kg; MK801, 0.5 mg/kg; PCP, 7.5 mg/kg; amphetamine, 6.0 mg/kg and scopolamine, 2 mg/kg. Doses of DOI, and MK801 were selected based on previous studies (Gonzalez-Maeso et al 2007; Fribourg et al 2011; Moreno et al 2011; Kurita et al 2012; Ibi et al 2017). Doses of PCP, amphetamine and scopolamine were selected based on previous studies (Fell et al 2008; Woolley et al 2008; Lavreysen et al 2015), and on pilot dose-response assays (data not shown).…”
Section: Methodsmentioning
confidence: 99%
“…HSVmGlu2, HSV-mGlu2ΔTM4N, or control HSV-GFP was injected into the frontal cortex by stereotaxic surgery according to standard methods (Kurita et al 2012; Moreno et al 2012; Ibi et al 2017). Mice were anesthetized with a combination of ketamine (100 mg/kg) and xylazine (10 mg/kg) during the surgery.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation